DINAMIKA DAN PENGENDALIAN SISTEM QUADRUPLE TANK MENGGUNAKAN CONTROLLER PI-PID DENGAN METODE DETUNING - Azizah, Zahrotul (Journal of Research and Technology, 2020)
In general, industrial processes have characteristics as multivariable processes where the variables interact with one another which causes poor performance. Quadruple tank is a Multi Input Multi Output (MIMO) system that can be used to analyze dynamics and process control schemes with strong interactions. The design is simple but can represent complex systems in the industry so that a reliable controller can be tested using this system. Tuning controller parameters using Ziegler-Nichols only work well for single loops, therefore detuning controllers are needed using the BLT and Mc Avoy methods. The research method is to make mathematical models and determine the specifications of quadruple tanks. Next make a process simulation and identify the transfer function with the step test method. Interaction analysis using the Relative Gain Array (RGA) method. Tuning controller parameters using the Ziegler-Nichols method is then detuned using the BLT and Mc Avoy methods. Simulation of quadruple tank systems both open loop and closed loop can run well and can be used to test the reliability of PI-PID controllers with BLT and Mc Avoy detuning. Based on IAE values, controller with Mc Avoy detuning are superior compared to controllers with BLT detuning, both at level and temperature controllers.